Stratifying breast cancer patients by baseline risk of cardiotoxic complications linked to chemotherapy - Zhenisgul Tlegenova; Saule Balmagambetova; Bekbolat Zholdin; Gulnara Kurmanalina; Iliada Talipova; Arip Koyshybaev; Dinara Nurmanova; Gulmira Sultanbekova; Mira Baspayeva; Saule Madinova; Kulparshan Kubenova; Ainel Urazova (National Scientific Medical Center, 2023)
A majority of modern antitumor pharmaceuticals are accompanied by cardiotoxicity. The study aims to present practical approaches to stratifying the baseline risk of antitumor therapies' cardiotoxicity in patients newly diagnosed with breast cancer started on anthracyclines and/or trastuzumab. Material and methods: Stratifying the risks of antitumor therapy was carried out according to the European Society of Cardiology recommendations. A therapist examined all patients for existing cardiovascular diseases and risk factors detection. The blood levels of glucose, cholesterol, creatinine, cardiac troponin I, and brain natriuretic peptide were determined. Electrocardiography and echocardiography with an assessment of the myocardium global longitudinal strain were performed. Results: In total, 128 breast cancer patients with a mean age of 54.3±11.0 years were included in the study. Of them, 84.4% had tumor stages I and II, and 21.1% were HER2-positive. Chronic heart failure and ischemic heart disease were detected in 2.3%.  Among the risk factors, the most common were arterial hypertension (51.6%), obesity (29.7%), age 65-70 years (18%), significant smoking history (15.6%), and diabetes mellitus (11.7%). Elevated cardiac troponin I and brain natriuretic peptide baseline levels were present in 5.5% and 7.0% of patients, respectively. To a high-risk group for cardiotoxic complications, 7.8% were allocated, 35.7% were assigned to the moderate-risk group, and 54.7% had low risk. High/very high and moderate-risk patients (43.5%) were referred to a cardiologist. Cardioprotective treatment was started immediately in high/very high-risk patients. Conclusion: All revealed differences between the cardiovascular risk groups were related to age, cardiovascular system condition, and the severity of comorbid pathologies. The baseline stratification of patients into risk groups is a crucial step in preventing the cardiotoxicity of anticancer therapy. Comprehensive assessing the patient's condition before and during chemotherapy allows for avoiding the development of fatal cardiovascular complications in at-risk patients.